The interrelatedness of error prevention and error management - Van der Byl, Connie A.; Vredenburg, Harrie (Frontiers in Psychology, 2023)
We study failure in organizations to understand and ideally prevent reoccurrence. Failures are often a combination of errors and have negative organizational outcomes while, interestingly, errors do not always lead to failure. Where error prevention falls short, error management, occurring ex ante, can enable learning. In this study, we examine mistakes made as Suncor Energy, Canada’s largest integrated oil company, adopted new technology to access untapped reserves. Errors led to environmental noncompliance charges and a fine. Through unique access granted by a creative sentencing order we obtained candid observations and reflections in interviews conducted with 50 Suncor employees and 21 stakeholders from outside the organization. We analysed the data using qualitative methods to determine that a pre-existing error management culture (EMC) dominated in the organization while error prevention measures were deficient. This is surprising given the complexity of the business and the importance of safety. We show that a balance between error prevention and error management is difficult to achieve owing to the contradictory nature of these approaches. While the extant organizational error literature identifies the complementary aspect of error prevention and error management it does not consider their interrelatedness - how one affects the other. We find that the dominating error management culture contributed to error prevention processes that were misapplied, informal or absent. This highlights the need for deliberate examination of error approaches especially as the business context shifts.